None of this is true : a novel [large type] - Jewell, Lisa (Thorndike Press large print top shelf., 2023)
"Celebrating her birthday at her local pub, podcaster Alix Summers crosses paths with a woman called Josie Fair. A few days later, Alix and Josie bump into each other outside Alix's children's school. Josie has been listening to Alix's podcasts and thinks she might be an interesting subject for her series. Slowly Alix starts to realize that Josie has been hiding some dark secrets, and before she knows it, Josie has inveigled her way into Alix's life. But, as quickly as she arrived, Josie disappears. Only then does Alix discover that she has become the subject of her own true crime podcast, with her life under mortal threat. Who is Josie Fair? And what has she done?"--